Pengembangan Komik Digital Berbasis Flipbook Untuk Siswa Kelas V Sekolah Dasar di Kecamatan Pati Kabupaten Pati - Asna Mariatul Kibtiyah (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to analyze needs, describe the development design, prove the feasibility and prove the effectiveness of flipbook-based digital comic media for fifth grade elementary school students in Pati District, Pati Regency. This research is a research development or Research and Development (R&D) using the Borg and Gall model development method which aims to develop flipbook-based digital comic learning media by paying attention to three quality aspects, namely valid, practical and effective. Qualitative data collection techniques through documentation, interviews and observations, while quantitative data collection techniques through tests and questionnaires. Data analysis is in the form of initial data before research, product development process data, product feasibility data and data on the effectiveness of flipbook-based digital comic learning media. The results of this study indicate that the level of need for social studies learning media in the form of digital comics based on flipbooks is quite high. Next, in designing flipbook-based digital comics through the sparkol application, there are several stages to go through which consist of: 1) Entering the sparkol videoscribe application; 2) Create and design digital comics with the help of the sparkol videoscribe application as well as voice over based on the storyline that has been made; 3) designing books using adobe photoshop; 4) make digital comics into book form with the help of a flipbook application called pdf pro; 5) digital comics that are already in the form of flipbooks are converted into android applications with the help of website 2 apk builder; 6) Digital comics are also made in a portable form so that they can be used via a PC or laptop. Next, The overall average score of validation from linguists, materials, and media experts is 3.31; 3.48 and 3.39 where all three are included in the "Very Eligible" criteria. Eligibility is also supported by the results of student and teacher questionnaire responses which show an average score of 3.31 and 3.25 with the criteria of "Very Good" and "Good". The use of flipbook-based digital comics is effective in helping students understand the concept of the role of the economy in an effort to improve people's lives and critical thinking skills of fifth grade elementary school students in Pati District, Pati Regency based on the results of Paired Sample T-test < 0.05 namely 0.049 and 0.048, which strengthened by the results of the Independent Sample T-test <0.05, namely 0.004 and 0.011.